Analyzing the Content of Physics Books in Light of Visual Thinking Skills - Al-Tamimi, Hanan Mohammad; Al-Mushaigeh, Latifa Mohammad (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to analyze the content of physics books in the light of visual thinking skills who should building a list of visual thinking skills to be included in the content of high school physics books, and to reveal the availability of these skills in the content of books. To achieve the objectives of the study, the descriptive approach was followed in the manner of content analysis, where the study community included and assigned all the physics books prescribed to secondary school students in Saudi Arabia, for the academic year 1441/1442 H, which numbered (4) books. The study tool consisted of a content analysis card built in the light of visual thinking skills. The study concluded to:The average ratio of visual thinking skills (75.9%) in the physics book (1), a (71.9%) in the physics book (2) with a high availability, and (74.7%) in the physics book (3) with high availability. A ratio of (66.6%) in the physics book (4) with medium availability. Visual thinking skills in the content of high school physics books in Saudi Arabia are available in a high range, and in varying proportions on six main skills. The skill of visual discrimination came first (86.6%), followed by the skill of representation of information (84.4%), the skill of analyzing information (72.8%), then the skill of extracting meanings (67.4%), then the skill of linking relationships by (65.4%), and then the interpretation of information skill (57.1%).On the light of the previously-mentioned results, the research concluded with a number of recommendations. The most important recommendation is to activate the skill of linking relationships, interpreting information, and illustrating meanings in a better way through visual aids found in the book of physics for the secondary level students. In the light of previous findings, the researcher made a number of recommendations.
Keywords: content analysis; visual thinking skills; physics books